Prognostic Factors in Patients with Multiple Recurrences of Well-Differentiated Thyroid Carcinoma. (15th October 2009) - Holler, Theresa; Theriault, Jenna; Payne, Richard J.; Clark, Jonathan; Eski, Spiro; Freeman, Jeremy L.
Abstract : Introduction. Patients with multiple recurrences of well-differentiated thyroid carcinoma (WDTC) have markedly reduced overall survival when compared with those who have≤ 1 recurrence of their disease. The purpose of this investigation is to identify prognostic factors for mortality in this subgroup. Methods. Patients with multiple recurrences of WDTC were retrospectively identified from the thyroid cancer database at Mount Sinai Hospital, Toronto (1963–2000). Data on patient, tumor, and recurrence characteristics were collected, and each patient was given aMACIS score. Results. A total of 31 patients were identified (11 male, 20 female; 16–83 years). Using univariate analysis, age> 45, stageIII / IV disease, distant metastasis, vascular invasion, MACIS score> 6, and time to recurrence of< 12 months were found to be significant predictors for mortality in this subgroup. Conclusions. Patients with multiple recurrences of WDTC follow a distinct clinical course, marked with multiple treatment failures and a substantial risk of mortality.